Interventions with men for gender equity: criticism of individualizing approaches - Fonseca, Vanessa do Nascimento (Revista Crítica Histórica, 2022)
The article makes a brief mapping of how interventions with men have been configured since the 1970s, analyzing the individualizing and behavioral character that has been built for this type of work, based on feminist criticisms that differentiate patriarchy from sexist behavior. We start from the assumption that men are important allies in facing the harmful effects of gender. However, in addition to thinking about their male chauvinistic behaviors, among themselves, seeking individual compensation arising from the changes of male chauvinism, their engagement in the fight against a system that articulates different power relations, normalizing subjects from colonial, capitalist, intersected cisheterosexuals and sexists.